Efficacy and tolerability of triple sequential combination therapies with selexipag in patients with pulmonary arterial hypertension: insights from a single-centre study - Tokgöz, Hacer Ceren; Kültürsay, B.; Tanyeri, S.; Hakgör, Aykun; Keskin, Bengisu; Buluş, Çağdaş (My University, 2024)
...
Keywords: Cardiac & Cardiovascular Systems; Cardiology; Meeting Abstract